On ideas of evolution and the evolution of ideas: communicating traditions of scientific enquiry - Winder, Nick; Winder, Isabelle; Jefferson, Bruce; Jeffrey, Paul (Open Science Framework, 2017)
That there was variation in the theories expounded by the major early thinkers on evolution is well established. What is less effectively articulated is how their intellectual ambitions and approaches to interpreting evidence reflect a deep-rooted difference in their views on what sort of systems, and problems evolution deals with; insights which speak directly to contemporary debates about how we communicate the nature of science with consequences for learning practice. We provide a re-reading of the perspectives adopted by those who formulated the central concepts of evolutionary theory to expose slender but persistent differences of emphasis. Our analysis contrasts the approaches to enquiry of three voyaging naturalists; Charles Darwin, Thomas Henry Huxley, and Alfred Russel Wallace. This potted history is used to illustrate the relationship between different traditions of scientific enquiry, specifically the natural philosophy approach characteristic of Wallace’s work and the later Neo-Darwinists; Huxley’s more empirical, natural history approach that anticipated punctuated equilibria, and Darwin’s emphasis on agency and choice, which suggests a more humanistic mind-set. These understandings are used to propose a model of the structure of evolutionary science which has broader value as a motif for exploring and communicating the transitions between different modes of enquiry.
Keywords: Darwin; Evolution; Huxley; Science education; Scientific enquiry; Wallace